Exl protein specifically binds BLE1, a bicoid mRNA localization element, and is required for one phase of its activity. - Macdonald, P.M.; Leask, A.; Kerr, K. (Proceedings of the National Academy of Sciences of the United States of America, 1995)
Localization of mRNAs, a crucial step in the early development of some animals, has been shown to be directed by cis-acting elements that presumably interact with localization factors. Here we identify a protein, exl, that binds to BLE1, an RNA localization element from the Drosophila bicoid mRNA. Using mutations in BLE1, we demonstrate a correlation between in vitro exl binding and one phase of in vivo localization directed by BLE1, implicating exl in that localization event. Furthermore, the same phase of localization is disrupted in exuperantia mutants, suggesting that exl and exuperantia proteins interact. Identification of a protein that binds specifically to an mRNA localization element and acts in mRNA localization opens the way for a biochemical analysis of this process.